Faktor-Faktor Yang Mempengaruhi IbuMemijatkan Bayi Ke Dukun BayiDi Desa Tunggul Sragen - Putri, Ria Devi, Irdawati, S.Kep.,Ns.,M.Si.Med (2016)
Baby massaging done regularly will improve the katekolamin hormone (epinefrin dan norepinefrin) able to trigger growth and development stimulation because could be improve the eating passion, improving body weight, and stimulus of structure growth and also brain function. The infant massage which was done by midwife or phsiotherapy. At the research find the phenomenon of role of traditional birth attendants which still big. The cultural was representing the factor having an effect on big to choice the baby massaging to traditional birth attendants. This research was purpose to identify factors affecting the mother seek traditional birth attendants to massage their baby in Tunggul Village Sragen. This research was quantitative research with cross sectional design. Population taken in this research was mother having age baby 0-12 month was the baby massaging to traditional birth attendants of last 3 month in Tunggul Village Sragen. Sample in this research was all population members. The questioner was used as research instrument. The data analyze was using multiple linear regressions analyze for 5% significant level. The multiple linear regressions analyze result with coefficient regression value for knowledge variable equal to +0,001, coefficient regression value for cultural variable equal to +0,249, coefficient regression value for perception variable equal to +0,064, coefficient regression value for attitude variable equal to +0,127, coefficient regression value for family support equal to +0,011, coefficient regression value for information variable equal to +0,285, coefficient regression value for economy variable equal to +0,012, and coefficient regression value for social environment equal to +0,642. Variable which significant have an effect on was cultural, information and social environment. All of variable with the positive parameter so that all variable improve risk. The conclusion for this research was Simpulan dari penelitian most having an effect on factor to the baby massage behavior to traditional birth attendants that was social environment (44,14%), Information (22,10%), cultural (19,81%), attitude (7,85%), perception (4,42%), economy (0,91%), family support (0,61%), knowledge (0,10%).